THE EFFECTIVENESS OF THE COLLABORATIVE LEARNING MODEL ON TRIGONOMETRY TOPIC OF SENIOR HIGH SCHOOL STUDENT GRADUATE X USING OPEN-ENDED APPROACH - Nurhayati Nurhayati; Karyati Karyati (STKIP Singkawang, 2016)
This study aimed to describe the effectiveness of collaborative learning using open-ended approach and open-ended approach in terms of problem solving skillss students. This study is a quasi-experimental research with the entire population of ten graduate science students of SMA Negeri 2 Ngaglik, Sleman, Yogyakarta which consists of four classes. The research samples were randomly selected from the four existing classes, in order to obtain class X MIPA 3 to be given collaborative learning model using open-ended approach and class X MIPA 1 to be given open-ended approach. Data analysis technique consists of one sample t-test used to investigate the effectiveness of collaborative learning model using open-ended approach and open-ended approach. The results show that collaborative learning model using open-ended approach is effective in terms of student’s problem solving skillss of SMA Negeri 2 Ngaglik, Sleman, Yogyakarta. But, open-ended approach isn’t effective in terms of student’s problem solving skillss of SMA Negeri 2 Ngaglik, Sleman, Yogyakarta.